Lung clearance index and moment ratios at different cut‐off values in infant multiple‐breath washout measurements. Issue 12 (23rd May 2016) - Egger, Barbara; Jost, Kerstin; Anagnostopoulou, Pinelopi; Yammine, Sophie; Singer, Florian; Casaulta, Carmen; Frey, Urs; Latzin, Philipp
Summary: Background: Multiple‐breath washout (MBW) is increasingly used for infant lung function testing. Current guidelines recommend calculating lung clearance index (LCI) and functional residual capacity (FRC) at 2.5% of normalized tracer gas concentration, without clear recommendation for moment ratios (MR). Whether the 2.5% cut‐off has the highest discriminative power to detect ventilation inhomogeneity in infants with lung diseases is unknown. Methods: We used sulfur‐hexafluoride MBW measurements from 32 infants with cystic fibrosis, 32 preterm infants, and 32 healthy controls at postmenstrual age of 41–54 weeks. We compared the discriminative power to detect pathological values above the upper limit of normal for 12 different cut‐offs between 20% and 1.5% for first and second MR (MR1, MR2), LCI, and FRC. Results: MR and LCI results changed significantly at different cut‐offs. Mean MR2 in infants with cystic fibrosis increased from 2.4 to 7.2 units between 20% and 1.5% SF6 . The ability of MR and LCI to discriminate between health and disease increased significantly with lower cut‐offs. The 1.5% cut‐off showed highest discriminative power: in infants with cystic fibrosis pathological MR2 values were found in 27 out of 89 (30%) and for LCI in 28/89 (32%). In preterm infants, pathological MR2 values were detected in 39 out of 73 (53%), and for LCI in 35/73 (48%). FRC remained stable throughout the washout. Conclusion: In infants, the diagnostic performance of MBW strongly depends on the point of analysis. The cut‐off with the highest discriminative power to detect ventilation inhomogeneity in infants with cystic fibrosis and after preterm birth was at 1.5% tracer gas concentration.Pediatr Pulmonol. 2016;51:1373–1381. © 2016 Wiley Periodicals, Inc.